INNOVATIVE TEACHING METHODOLOGY BASED ON PAREMICS IN EDUCATION FOR SCHOOL STUDENTS (International journal of artificial intelligence, 2026)
This article highlights the pedagogical importance of using paremic tools - proverbs, sayings, wise sayings and folk expressions - in teaching education to students of secondary schools. Also, the issues of developing students' moral thinking, respect for national values, independent thinking and communicative competence through the use of innovative teaching methods based on paremics are analyzed.